DIREKTIF DALAM DAKWAH: REPRESENTASI KEKUASAAN DALAM WACANA TGK. HAMZANWADI - PUTU KERTI NITIASIH (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2007)
Abstract An analysis on the speech acts used by TGK. Hamzanwadi as a communicative strategy to influence his viewers to do something, showed that the highest percentage is on the use of directive which was due to the characteristic of a sermon as a religious genre which is mostly indoctrination in nature. The purpose of the directives were: to ask, to prohibit, to order, to instruct, and to support which represent the power in TGK. Hamzanwadi?s dakwah.. Kata-kata kunci: Tindak tutur, direktif, kekuasaan, dakwah.